HUBUNGAN PENGETAHUAN DAN SIKAP IBU HAMIL DENGAN KEPATUHAN IMUNISASI TETANUS TOXOID (TT) - Anggriani, Gustika; Septiana, Maria; Anggella Ariesta (Jurnal Kesehatan dan Pembangunan, 2025)
Tetanus toxoid (TT) immunization is an injection of the tetanus vaccine to increase immunity as an effort to prevent tetanus infection. The aim of the research is to determine the relationship between knowledge and attitudes of pregnant women with compliance with tetanus toxoid (TT) immunization at BPM Umi Kalsum, Prabumulih City in 2024. Research methods analytical, using a Cross Sectional approach. The population of this study were all pregnant women who visited BPM Umi Kalsum when conducting research in March 2024. The sample taken in this study used the accidental sampling technique, namely 40 people. The research instrument is a questionnaire. The results of the research based on univariate analysis showed that of the 40 respondents there were 28 respondents (70%) who had tetanus immunization and 12 respondents (30%) who had not carried out tetanus immunization, there were 28 respondents (70%) who had good knowledge and 12 respondents (30%) %) who had less knowledge, there were 30 people (75%) who had a supportive attitude and 10 respondents (25%) who had an unsupportive attitude. Of the 28 respondents who had good knowledge, 24 respondents (60%) carried out TT immunization, while of the 12 respondents who had poor knowledge, 4 respondents (10%) complied with TT immunization and of the 30 respondents who had a supportive attitude, there were 25 people (62, 5%) had TT immunization, while of the 10 respondents who had an unsupportive attitude, 3 people (7.5%) had TT immunization. Conclusion: There is a significant relationship between knowledge and compliance with tetanus toxoid (TT) immunization with a P value of 0.003 < ? 0.05 and there is a significant relationship between maternal attitudes and compliance with tetanus toxoid (TT) immunization with a P value of 0.005 < ? 0.05.